FAKTOR INTERNAL DAN EKSTERNAL DALAM PENGEMBANGAN OBJEK WISATA PEMANDIAN AIR TERJUN LUBUK TAMPURAUNG DI KECAMATAN KURANJI KOTA PADANG - Zeshasina Rosha; Helmawati Helmawati; Ethika Ethika; Hasnul Fikri (Jurnal Apresiasi Ekonomi, 2022)
Lubuk Tempurung Waterfall Bathing Attraction is the only tourist attraction in Belimbing Village, Kuranji district, Padang City which is equipped with waterfalls. This tourist attraction has not received guidance yet from the government or investment from the private sector. The purpose of the research is to find out the strengths, weaknesses, opportunities, and threats in the development of Lubuak Tampuruang Waterfall Bathing Attraction. This study uses SWOT analysis, which analyzes internal factors (strengths and weaknesses) and external factors (opportunities and threats). The main data are collected through the questionnaire. The results of the research are, first, the main strength is the water attraction equipped with a waterfall is easy to reach because it is not so far from the center of Padang City. Second, the weakness is the road to the tourist attraction is inadequate. Third, the opportunity is the high desire to travel and recreation. Fourth, the threat that needs to be addressed is the influx of negative cultural influences from outsiders and interactions between local communities and global tourists. The strengths-opportunities strategy suggested in the development of Lubuak Tampuruang Waterfall Bathing Attraction is maximizing the power to achieve opportunities that will make this attraction better than ever.Keywords: external factors, internal factors, tourism, SWOT, Lubuak Tampuruang